Impact of COVID-19 on Postgraduate research in Obstetrics and Gynaecology: Challenges, Solutions and Opportunities - Rafat, Dalia; Tamkin, Khan (Bangladesh Journal of Medical Science, 2021)
Objectives: COVID-19 pandemic has affected medical services and facilities throughout the world. This has resulted in unavoidable decline in postgraduate training and learning in different medical specialties. There has been reduction in all aspects of training and learning of Obstetrics and Gynaecology (OBG) residents in general and research training in particular. At the time of the study, although limited institutions have started to put some efforts to resume and endure resident research in OBG but still there are no uniform adaptive measures which can be implemented in all of the institutions. The present study was conducted with the aim to assess challenges faced by OBG residents in doing research during COVID-19 pandemic in a government medical college of India. We also assessed the helpfulness and support provided by the Thesis Mentorship Programme (TMP) of the department during pandemic. Material and Methods: A self developed semi structured, pre-validated questionnaire was mailed to the residents of the OBG training program of our medical college. It was completed anonymously by them after accepting an informed consent. Results: 21 postgraduates from the second and third year OBG residency participated in this cross-sectional study. We found that COVID-19 pandemic was associated with a significant research training impairment. There was “some” to “complete interruption” in the various research activities of the residents. The research aspect most severely affected was data collection. Also majority of residents were satisfied with the support offered by the TMP of the department in sustaining resident research during pandemic. Conclusion: COVID-19 has significant and critical implications for the resident research training in OBG.The TMP and similar experiences also helps residents in continuing research during untoward circumstances. Bangladesh Journal of Medical Science Vol.20(5) 2021 p.77-84